The effectiveness of job satisfaction in mediating work motivation and work discipline towards employee performance - Riwayati, Hedwigis Esti; Winarti, Ch. Endah; Cahaya, Yohanes Ferry; Khairunnisa, Khairunnisa (Jurnal Ekonomi dan Bisnis, 2025)
The research to explore whether work motivation and work discipline through mediation by work satisfaction towards the performance of employee at the Directorate of Operations in PT Bussan Auto Finance's Head Office. Quantitative descriptive has been chosen as the study design. The population and sample of this research were all permanent employees at Directorate of Operations of PT Bussan Auto Finance’s Head Office with total of 77 people who were determined by non-probability sampling technique, type of saturated sampling or census. Then these data brought to analyzed through the use of PLS-SEM method in order to measures the structural models. The research results shows that both of motivation and discipline did not affect the performance of employee. Work satisfaction significantly effects the performance. But work motivation and discipline would have significant positive effect if it was mediated by job satisfaction. This research will bring new impact in which it stated that work motivation and discipline have no influence towards the employee performance, so this novelty would need further research in similar industries.